2014
DOI: 10.1021/cg401181j
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Ba2LnFeNb4O15 (Ln = Pr, Nd, Sm, Eu) Relaxor Single Crystals

Abstract: Ba2LnFeNb4O15 (Ln = Pr, Nd, Sm, and Eu) single crystals were grown from high-temperature solution under controlled atmosphere. Chemical, structural, and dielectric characterizations were performed on four crystals with tetragonal tungsten bronze (TTB) structure. The main difference between the four crystals’ compositions is the proportion of rare-earth, as well as vacancies, located in the square site. All crystals displayed an incommensurately modulated structure at room temperature in the paraelectric state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
(55 reference statements)
4
30
0
1
Order By: Relevance
“…This phenomenon could be related to the one observed in corresponding ceramics and single-crystals, in which the insertion of smaller rare earths (i.e. Nd or Eu instead of La) leads to and off-stoichiometry that could involve oxygen losses, which can be induced during the processing [14,30,31]. It was reported that the leakage current of oxide films could be reduced by activated oxygen annealing [39].…”
Section: Dielectric Characterization Of Ba 2 Lnfenb 4 O 15 Thin Filmsmentioning
confidence: 61%
“…This phenomenon could be related to the one observed in corresponding ceramics and single-crystals, in which the insertion of smaller rare earths (i.e. Nd or Eu instead of La) leads to and off-stoichiometry that could involve oxygen losses, which can be induced during the processing [14,30,31]. It was reported that the leakage current of oxide films could be reduced by activated oxygen annealing [39].…”
Section: Dielectric Characterization Of Ba 2 Lnfenb 4 O 15 Thin Filmsmentioning
confidence: 61%
“…In recent years, the research dedicated to novel TTB ferroelectric and ferroelectric-related (i.e., relaxors) materials has undergone a revival, with Ba 6 FeNb 9 O 30 (BFNO) as a starting point; many related compositions [28][29][30][31] or solid solutions, usually containing lanthanides [32][33][34][35][36], were studied. Arnold and Morrison [5], and subsequently Liu et al [37], showed that these compounds display relaxor-type behaviour [38][39][40], with the peak maxima in the dielectric permittivity occurring in the temperature range 130-150 K. Earlier data indicated that BFNO is not electrically homogeneous [34], with oxygen vacancy gradients due to the variable oxidation state of Fe (Fe 3?…”
Section: Introductionmentioning
confidence: 99%
“…These impurities are also found in Ba 4 Ln 2 Fe 2 Nb 8 O 30 ceramics. 20,21 Figure 2 presents the surface morphology of the sintered ceramic exhibiting homogeneous microstructure with rod-like grains and low porosity. The relative density of the ceramic is 95.2% (the relative density is calculated by the ratio of apparent density and true density).…”
Section: Resultsmentioning
confidence: 99%